Cholinergic innervation of the guinea-pig isolated vas deferens - Solanki, Pravesh (2007)
Recently, a cholinergic neurogenic component of contraction has been characterised in the aganglionic mouse vas deferens. In this paper, a cholinergic component of contraction in the guinea-pig vas deferens is characterised pharmacologically. A residual, tetrodotoxin-sensitive (TTX, 0.3 μM), neurogenic contraction was revealed after prolonged exposure (5 h) to the adrenergic neurone blocker bretylium (20 μM) or in the presence of prazosin (100 nM) and α,β-methylene ATP (1 μM), a purinergic agonist which desensitizes P2X receptors. The bretylium-resistant component was potentiated by the acetylcholinesterase (AChE) inhibitor neostigmine (10 μM) and inhibited by the muscarinic-receptor (mAChR) antagonist cyclopentolate (1 μM). Nicotine (30 μM) enhanced the bretylium-resistant component. Neostigmine increased the second component of contraction in the presence of prazosin and α,β-methylene ATP, whilst yohimbine (1 μM), an α(2) adrenergic receptor antagonist, enhanced both the first and second components of the electrically evoked contraction. These enhanced contractions were blocked by cyclopentolate in both cases. Nicotine enhanced the cholinergic component of contraction revealed by neostigmine but failed to have any detectable effects in the presence of cyclopentolate. Neostigmine alone increased the slow component of contraction which was reversed by cyclopentolate to control levels. The M(3) receptor-antagonist 4-DAMP (10 nM) markedly inhibited the cholinergic component of contraction to a level comparable with cyclopentolate. Laser microscopy has shown that neostigmine also increased the frequency of spontaneous Ca(2+) transients remaining in smooth muscle cells after perfusion with prazosin and α,β-methylene ATP, an effect blocked by 4-DAMP. These experimental data show that there is a functional cholinergic innervation in the guinea-pig vas deferens whose action is limited by acetylcholinesterase, blocked by cyclopentolate and mediated through M3 receptors. Moreover, by blocking the cholinesterase, the increased amount of ACh generates spontaneous Ca(2+) transients in smooth muscle cells.